Talent Enrichment and Operational Sustainability in the Nigerian Telecommunication Sector - Akpotu, Christopher; Tamunosiki-Amadi, Jasmine (Advances in Social Sciences Research Journal, 2019)
Organisations are striving towards improved operational modes that enhance responsiveness to customer needs. One of the strategically considered means is talent enrichment practices for employees who are talent repository for firms. This study examined the empirical link between talent enrichment and operational sustainability. A sample of 216 employees the telecommunication sector in Nigeria was surveyed using questionnaire instrument. The data showed a positive and significant relationship between the constructs examined. This was noticeably strong with targeted skill mapping and operational effectiveness measured by quality service delivery, process improvement and timelines in service delivery. It is clear from the findings that talent enrichment remains a strategic imperative that engenders effective and efficient operations in work organisations. The findings hold strong theoretical implications in terms of operationalization of the variables that has been hitherto viewed as unidimensional. Its value-driven implication in terms of managerial policy is underscored.